2021
DOI: 10.3389/fpls.2021.765070
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Grazing Disturbances on the Plant Diversity and Ecological Functions of Alpine Grassland Ecosystem on the Qinghai-Tibetan Plateau

Abstract: Grazing is one of the main human disturbance factors in alpine grassland on the Qinghai-Tibet Plateau (QTP), which can directly or indirectly influence the community structures and ecological functions of grassland ecosystems. However, despite extensive field grazing experiments, there is currently no consensus on how different grazing management approaches affect alpine grassland diversity, soil carbon (C), and nitrogen (N). Here, we conducted a meta-analysis of 70 peer-reviewed publications to evaluate the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 81 publications
(124 reference statements)
1
11
0
Order By: Relevance
“…This study found that grazing evidently elevated the SH ( Shan et al, 2011 ; Zhang et al, 2019 ; Li et al, 2021 ; Liu et al, 2021 ), BD, pH ( Blank et al, 2006 ; Ajorlo et al, 2011 ; Rong et al, 2022 ), ACa, AMg ( Jusoff, 1988 ; Blank et al, 2006 ), ßGC, ACP, and C limitation ( Goenster-Jordan et al, 2021 ), but decreased the WC and AP ( Niu et al, 2016 ; Sigcha et al, 2018 ; Chen et al, 2021 ; Fenetahun et al, 2021 ; Rong et al, 2022 ; Figure 1 ). The buffalo squeezed the soil pores that include those pores originally storing water and air, through treading, which caused soil compaction ( Ludvíková et al, 2014 ), elevated the bulk density ( Li et al, 2008 ; Zhan et al, 2020 ; Fenetahun et al, 2021 ; Wade et al, 2022 ) and soil hardness, and reduced soil water infiltration ( Daniel et al, 2002 ).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…This study found that grazing evidently elevated the SH ( Shan et al, 2011 ; Zhang et al, 2019 ; Li et al, 2021 ; Liu et al, 2021 ), BD, pH ( Blank et al, 2006 ; Ajorlo et al, 2011 ; Rong et al, 2022 ), ACa, AMg ( Jusoff, 1988 ; Blank et al, 2006 ), ßGC, ACP, and C limitation ( Goenster-Jordan et al, 2021 ), but decreased the WC and AP ( Niu et al, 2016 ; Sigcha et al, 2018 ; Chen et al, 2021 ; Fenetahun et al, 2021 ; Rong et al, 2022 ; Figure 1 ). The buffalo squeezed the soil pores that include those pores originally storing water and air, through treading, which caused soil compaction ( Ludvíková et al, 2014 ), elevated the bulk density ( Li et al, 2008 ; Zhan et al, 2020 ; Fenetahun et al, 2021 ; Wade et al, 2022 ) and soil hardness, and reduced soil water infiltration ( Daniel et al, 2002 ).…”
Section: Discussionmentioning
confidence: 69%
“…Grazing could decrease soil porosity ( Tang et al, 2019 ) and increase soil bulk density ( Binkley et al, 2003 ; Davidson et al, 2017 ; Zhang et al, 2018b ; Sun et al, 2019 ; Lai and Kumar, 2020 ; Fenetahun et al, 2021 ). These could result in a decline in the air and water permeability ( Daniel et al, 2002 ; Zhang et al, 2018b ) and soil moisture ( Hou et al, 2014 ; Li et al, 2021 ; Liu et al, 2021 ). However, grazing also increased soil pH ( Binkley et al, 2003 ; Hao and He, 2019 ; Fenetahun et al, 2021 ; Li et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plants’ diversity patterns have been attributed to spatial factors, climate factors, abiotic factors, or biotic factors in previous studies, and these patterns generally exhibit either monotonically declining or hump-shaped diversity patterns with increased elevation [ 49 , 50 , 51 ]. Plant alpha diversity had no strong relationship with soil bacterial alpha diversity and other environmental factors in the current study, although it may be affected by human disturbances [ 52 ]. Soil bacterial Shannon index was closely related with climate factors (elevation, MAT, and MAP) and soil nutrients (soil moisture, pH, and SOC).…”
Section: Discussionmentioning
confidence: 98%
“…In alpine meadow, N and P addition significantly affect t plant communities ( Ma et al., 2021 ), soil microbial community and enzyme activities ( Zi et al., 2022 ), and microbial functional genes ( Xiao et al., 2022 ). In alpine steppe, N and P application led to an increase in aboveground biomass ( Li et al., 2021b ), and increased intensity of bacteria and fungi ( Li et al., 2021c ), also affected the plant functional traits ( Li et al., 2022d ). Meanwhile, grazing increased herbage respiration in summer, presumably through stimulation of gross photosynthesis ( Yuan et al., 2022 ), and changed plant community composition and reduced stochasticity of soil microbial community assembly of alpine grasslands ( Li et al., 2022a ).…”
mentioning
confidence: 99%